Resistin is Associated with Inflammation and Renal Function, but not with Insulin Resistance in Type 2 Diabetes - Rzepa, Łukasz; Peller, Michał; Eyileten, Ceren; Rosiak, Marek; Kondracka, Agnieszka; Mirowska-Guzel, Dagmara; Opolski, Grzegorz; Filipiak, Krzysztof J.; Postuła, Marek; Kapłon-Cieslicka, Agnieszka (Hormone and Metabolic Research, 2021)
The aim of the study was to investigate the association of adipokines (resistin, leptin and adiponectin) with obesity, insulin resistance (IR) and inflammation in type 2 diabetes mellitus (T2DM). A total of 284 patients with T2DM were included. Concentrations of resistin, leptin, adiponectin, and inflammatory markers [high sensitivity C-reactive protein (hsCRP), tumor necrosis factor α (TNF-α), and interleukin 6 (IL-6)] were measured and homeostatic model assessment for IR (HOMA-IR) index was calculated. Resistin correlated negatively with estimated glomerular filtration rate (eGFR) and positively with hsCRP, TNF-α, IL-6, and white blood cell count (WBC). Leptin correlated positively with HOMA-IR, whereas adiponectin correlated negatively. Leptin also correlated positively with body mass index (BMI), waist circumference, IL-6, WBC and negatively with eGFR. Adiponectin correlated negatively with waist circumference, WBC, and eGFR. Multivariate logistic regression indicated lower eGFR and higher WBC and IL-6 as independent predictive factors of resistin concentration above the upper quartile (CAQ3), whereas female sex and higher BMI and HOMA-IR of leptin CAQ3, and lower HOMA-IR and older age of adiponectin CAQ3. In conclusion, in contrast to leptin and adiponectin, in T2DM patients, resistin is not associated with BMI and IR, but with inflammation and worse kidney function.
Keywords: resistin; adipokines; diabetes mellitus; inflammation; renal function; insulin resistance